Some Aspects of Seventeenth Century Malay via Thomas Bowrey's Bilingual Dictionary, Published in 1701 (KEMANUSIAAN The Asian Journal of Humanities, 2009)
This article presents a description and an analytical overview of Bowrey's bilingual dictionary, published in 1701. It examines the word entries (lemmas) found in the dictionary, including the content of the supplements of the dictionary. This article discusses some aspects of the morphology of oral Malay as found in the dictionary data, as well as some of the basic syntactic patterns and the nature of the sociolinguistic dimensions that are reflected in the dictionary. Some morphological and syntactic patterns identified in the dictionary are diachronically compared with either the forms found earlier in written text or those found later in contemporary oral Malay in order to estimate the authenticity and correctness of the forms. Some of the findings include the possibilities that the prefixes ber-, ba-, and me- and their variants could be allomorphic in 17th century oral Malay. Between the ber- and ba- variants, ber- seemed to have a broader function. It also seemed that only ber- had survived to the present day; the original function of the prefix ba- was likely taken over by either ber- or me- and their allomorphic variants. The syntactic data revealed five basic syntactic patterns. In the interrogative structures, the wh- questions seemed to favour placing wh- words in the initial position in a sentence, without any interrogative marker (-kah). The yes-no questions seemed to favour the echo variety. Although ialah was present, its corresponding adalah did not appear. The presence of adakah seemed to suggest the existence of the corresponding adalah. Bowrey probably did not remember this when writing the dictionary. Regarding the sociolinguistic dimension, the dictionary revealed that the pronominal form kitta (present-day kita) was used only as a first-person singular pronoun. While aku did exist at the time, there seemed to be no saya in 17th century oral Malay.